Pharmaceutical formulation : the science and technology of dosage forms - Tovey, Geoffrey D. (RSC drug discovery series, 2018)
Pharmaceutical Formulation provides an up to date source of information for all who wish to understand the principles and practice of formulation in the drug industry.